Low Yield of Cerebral Angiography in Adequately Occluded Aneurysms After Flow Diversion. Issue 6 (5th March 2018) - Chalouhi, Nohra; Patel, Purvee D; Atallah, Elias; Starke, Robert M; Chitale, Ameet; Lang, Michael; Tjoumakaris, Stavropoula; Hasan, David; Zarzour, Hekmat; Smith, Michelle J; Rosenwasser, Robert; Jabbour, Pascal
Abstract: BACKGROUND: Flow diversion has emerged as a highly effective treatment for intracranial aneurysms. OBJECTIVE: To assess the yield of further angiographic follow-up in aneurysms that have achieved adequate occlusion after treatment with the Pipeline Embolization Device (PED; Medtronic Inc, Dublin, Ireland). METHODS: This is a single-institution, retrospective study. Inclusion criteria were as follows: (1) patients with 1 or more aneurysms treated with PED, (2) available short-term (<12 mo) follow-up digital subtraction angiography (DSA), (3) complete (100%) or near-complete (>95%) occlusion on short-term follow-up DSA, and (4) available further angiographic follow-up (DSA, Magnetic Resonance Angiography (MRA), or Computed Tomography Angiography (CTA)). RESULTS: A total of 146 patients were identified. Aneurysm size was 8.4 ± 5.1 mm on average. Mean angiographic follow-up time was 29.7 ± 12.2 mo. On short-term follow-up DSA images, 132 (90.4%) had complete aneurysm occlusion and 14 (9.6%) had near-complete occlusion. Four patients (3%) had further DSA follow-up alone, 30 patients (21%) had further DSA and MRA/CTA follow-up, and 112 patients (76%) had further MRA/CTA follow-up alone. On further angiographic follow-up (DSA, MRA, and/or CTA), no patient had a decrease in the degree of aneurysm occlusion (recurrence) or required retreatment. Of the 14 patients with near-complete occlusion on initial DSA images, 7 patients (50%) progressed to complete aneurysm occlusion on further angiographic follow-up. CONCLUSION: This study did not find any diagnostic yield in repeating cerebral angiography in adequately occluded aneurysms with the PED. We do not recommend repeat angiographic follow-up once aneurysms have achieved complete occlusion with the PED unless clinically warranted.